Amoebic gill disease susceptibility of farm strain and wild strain Atlantic salmon (Salmo salar), and brown trout (Salmo trutta) post-smolts challenged with Paramoeba perurans - Botnevik, Henrik (The University of Bergen, 2021)
Masteroppgave i fiskehelse FISK399 MAMN-FISK